2001
DOI: 10.1046/j.1365-2036.2001.01102.x
|View full text |Cite
|
Sign up to set email alerts
|

The treatment of inflammatory bowel disease with 6‐mercaptopurine or azathioprine

Abstract: The thioguanine derivative, azathioprine, is a prodrug of 6‐mercaptopurine that is further metabolized by various enzymes present in the liver and gut. Azathioprine and 6‐mercaptopurine have been used in the treatment of inflammatory bowel disease, i.e. ulcerative colitis and Crohn’s disease, for more than 30 years. However, widespread use of azathioprine or 6‐mercaptopurine in inflammatory bowel disease is of more recent origin, the primary reason being a long‐standing debate on the efficacy of these agents i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
109
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(112 citation statements)
references
References 65 publications
(79 reference statements)
1
109
1
1
Order By: Relevance
“…Phase II, designed based on the results of phase I, used seven clinical strains of M. paratuberculosis of bovine or human origin and one M. avium strain, ATCC 35712, as a control. Some drugs to which M. paratuberculosis was not susceptible in phase I, specifically the SS drug family (SS, 5-ASA, and SP), were excluded, and AZA, a prodrug of 6-MP, was added to the trial (19,27).…”
Section: Drugs Testedmentioning
confidence: 99%
“…Phase II, designed based on the results of phase I, used seven clinical strains of M. paratuberculosis of bovine or human origin and one M. avium strain, ATCC 35712, as a control. Some drugs to which M. paratuberculosis was not susceptible in phase I, specifically the SS drug family (SS, 5-ASA, and SP), were excluded, and AZA, a prodrug of 6-MP, was added to the trial (19,27).…”
Section: Drugs Testedmentioning
confidence: 99%
“…The preferential increase of 6-MMP but not 6-TGN concentrations was observed in 5 of 8 patients with multiple dose escalations without the desired rise of 6-TGN Ͼ250 pmol/8 ϫ 10 8 Ery. Because AZA dosage increases based on 6-TGN concentrations did not show the desired increase in the latter, irrespective of TPMT, other independent variables must influence metabolite steady-state concentrations; variable bioavailability in active inflammatory bowel disease (34,35 ) is one candidate. Our previous observations in active Crohn disease compared with other chronic inflammatory systemic diseases are also in agreement with these findings (36 ).…”
Section: Discussionmentioning
confidence: 99%
“…7 m g / k g p e r d ay ) p r ove d t o b e e f f e c t ive i n maintaining remission in a French cohort of CD patients, which was lower than the dose used in clinical trials (2.5 mg/kg per day). Nielsen et al in their review in the year 2001, suggested a 0.25 ± 0.5 mg/kg daily initial (AZA equivalent) dose for the 6-MP, increasing to 1.0 ± 1.5 mg/kg daily [30] . Su and Lichtenstein, three years later, advocated "the optimal dose for the treatment of active CD is generally considered 2.5 mg/kg per day for azathioprine and 1.5 mg/kg per day for 6-MP" [17] .…”
mentioning
confidence: 99%